Vulnerability and strength in women's lived experiences of HIV: "it was sad that first day, but now I'm powerful - Allen, Chantelle (Division of Nursing and Midwifery, 2025)
HIV is a steadily growing epidemic that is affecting sub-Saharan Africa more than any other region in the world. Within this epidemic, more women than men are infected. Research has illustrated that women are vulnerable to HIV due to social constructs such as poverty and inequality as well as being biologically more susceptible to transmission . Despite this, little research has been done to describe the experience of women living with HIV within this context. The aim of this study was to describe the lived experience of HIV for women through an interpretative paradigm utilising hermeneutic phenomenology as a method. Four individual interviews were conducted with HIV-positive women, transcribed and analysed using a rigorous qualitative data analysis method. The initial findings were presented as themes to a focus group of HIV-positive women and developed further. The final themes were combined and written up as thick descriptions. Five themes emerged: (1) "When you first hear it. .. ", described participants experiences of receiving an HIV-positive diagnosis, (2) "I'm worried about rejection ... ", illustrated participants fears of stigma and discrimination, (3) "Holding your secret. .. ", explored how the participants attempted to protect themselves by keeping their HIV-positive status a secret, (4) "If I can disclose myself .. ", explored participants deliberations about r evealing their HIV status, and (5) "I've learned to live with it...", described how they also learned to live with HIV and accept their status over time. Participants felt overwhelmed and powerless as they were keeping their HIV status as a secret, protecting themselves in an environment where HIV was highly stigmatised and they were economically dependent on others. Simultaneously, they began to acknowledge their own value and meaning and regain control over their lives and care for themselves. Their lives were characterised by an ongoing tension between their contextual vulnerability and their newly discovered personal strength and resolve. These research findings are discussed within the framework of Van Manen's 'lifeworld existentials' of lived body, lived time, lived relationships and lived space (Van Manen 1990). Lived experience has intra-personal (lived body and lived time) and interpersonal (lived relationships and lived space) components and meanings. This study 's findings have implications for health policy-makers, health workers and ot her s t akeholders. It illustrates the valuable role that counselling, support groups and faith-based organisations can play. New dimensions are added to the curren t understanding of the role of disclosure and stigma, suggesting the need for different approaches to implementing interventions in this con text.